2022
DOI: 10.1186/s41018-022-00115-0
|View full text |Cite
|
Sign up to set email alerts
|

Social capital undergirds coping strategies: evidence from two informal settlements in Nairobi

Abstract: Understanding the nature and scope of existing social capital is essential to building the resilience of people living in vulnerable urban settings. This paper explores the question of how aid organisations can better utilise social capital to build the resilience of communities in slums. It specifically examines the relationship between social capital and urban vulnerability. The study used a mixed-methods approach to understand the diverse perspectives of social capital and uncover relationships that exist b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…For instance, evidence suggests that individuals might share community water resources within their social networks to meet water needs [ [46] , [47] , [48] ]. Several studies have demonstrated the significance of social capital on livelihoods and health outcomes [ [49] , [50] , [51] ]. Our study contributes to this body of work by demonstrating how livelihood interventions might, in turn, enhance or strengthen social capital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, evidence suggests that individuals might share community water resources within their social networks to meet water needs [ [46] , [47] , [48] ]. Several studies have demonstrated the significance of social capital on livelihoods and health outcomes [ [49] , [50] , [51] ]. Our study contributes to this body of work by demonstrating how livelihood interventions might, in turn, enhance or strengthen social capital.…”
Section: Discussionmentioning
confidence: 99%
“…Resource reciprocity is a common coping strategy for meeting basic needs among poor households,. [ 51 , 55 , 56 ]. For example, poor rural families in Ethiopia gather and share meals by reducing their portions to ensure that no one goes hungry [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This link between state social welfare system and social capital in the community is often overlooked (Rothstein and Stolle 2003). Mpanje at al. (2022) demonstrate the significance of social capital as a household coping strategy of vulnerable urban households.…”
Section: How Did Households Cope With the Ensuing Covid-19 Socioecono...mentioning
confidence: 99%
“…According to Wesonga, the national government's COVID-19 emergency programmes have only benefited the community leaders and their families, which has led to mistrust and divisiveness. Mpanje et al (2022) argue that government and donor programmes should be used to reinforce community social capital through utilization of community structures for proper and fair targeting of beneficiaries. This would create trust and community cohesiveness.…”
Section: The Shortfalls Of Social Protection Against the Covid-19-rel...mentioning
confidence: 99%